2016
DOI: 10.1039/c5gc02985f
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous recyclable nano-palladium catalyzed amidation of esters using formamides as amine sources

Abstract: Catalyzed by supported palladium nanoparticles, a decarbonylative amidation reaction between various aryl esters and formamides by C–O bond activation has been developed for the synthesis of amides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…A high‐resolution XPS Pd 3d spectrum of Fe 3 O 4 @SSAs@Pd NPs was treated with peak fitting and displayed in Figure b. It could be found that there were two main peaks with binding energy (BE) of 334.5 and 340.5 eV, corresponding to Pd(0) 3d5/2 and Pd(0) 3d3/2, implying the presence of Pd NPs in the final product. Then EDX analysis shown in Figure c was used to demonstrate the composition of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…A high‐resolution XPS Pd 3d spectrum of Fe 3 O 4 @SSAs@Pd NPs was treated with peak fitting and displayed in Figure b. It could be found that there were two main peaks with binding energy (BE) of 334.5 and 340.5 eV, corresponding to Pd(0) 3d5/2 and Pd(0) 3d3/2, implying the presence of Pd NPs in the final product. Then EDX analysis shown in Figure c was used to demonstrate the composition of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…A FULI GC-9790II equipped with a flame ionization detector (FID) detector was used to analysis the reaction mixture. 1 H nuclear magnetic resonance (NMR) and 13 C NMR spectra were recorded on a Bruker AV-II 500-MHz NMR spectrometer ( 1 H: 500 MHz, 13 C: 125.76 MHz) in CDCl 3 or DMSO-d 6 . The coupling constants J are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (500 MHz CDCl 3 ): δ 7.19-7.16 (m, 2H), 7.11-7.08 (m, 3H), 3.55 (s, 3H), 2.85 (t, J = 7.5 Hz, 2H), 2.52 (t, J = 8.0 Hz, 2H). 13 Methyl hexanoate (2p): 40 Colorless oil; yield: 94% (158.9 mg). Eluent: petroleum ether.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations